Advances in the study of ARR3 in myopia - Guo, Yi-Ming; Wei, Junhan; Wang, Jiaqi; Zhang, Guoyun; Bi, Jiejing; Ye, Lu (Frontiers in Cell and Developmental Biology, 2025)
The ARR3 gene (cone arrestin, OMIM: 301770) has gained significant attention as a pivotal factor in the etiology of myopia, particularly early-onset high myopia (eoHM). As a member of the arrestin gene family, ARR3 is predominantly expressed in cone photoreceptors, playing a crucial role in visual processing. Recent studies have identified specific mutations in ARR3 that correlate with an elevated risk of myopia development, highlighting its potential involvement in the disease’s pathogenesis. This review summarizes current advancements in elucidating the relationship between ARR3 and myopia, emphasizing genetic variations associated with refractive errors and their implications for myopia research and clinical management. We emphasize the necessity for further studies to elucidate the role of ARR3 in myopia, particularly regarding its impact on visual development and the genetic predisposition observed in specific populations.